An anti-freezing/drying, adhesive and self-healing motion sensor with humidity-enhanced conductivity. (1st February 2021) - Yang, Kaixiang; He, Jiaqing; Zhou, Qiang; Hao, Xiang; Yang, Haiyang; You, Yezi
Abstract: Flexible gels have shown great potential in electronic sensors, but their conductivity may decrease or even disappear after long-term or extreme temperature use. Here, a new class of conductive organohydrogel sensors was fabricated with multipurpose adhesion, anti-freezing/drying, excellent humidity-enhanced conductivity, and self-healing properties. By employing the appropriate glycerol/water ratio, the organohydrogel sensor can be used either under low (−30 °C) or high (60 °C) temperature, featuring for catching water from the environment to enhance the conductivity. This work hold promises for the fabrication of high-performance sensing material with multi-functional sensing and synergistic properties. Graphical abstract: We report an anti-freezing/drying, adhesive and self-healing motion/humidity sensor with humidity-enhanced conductivity. Image 1 Highlights: An anti-freezing/drying, adhesive and self-healing motion/humidity sensor has been developed. The humidity-enhanced conductive property provides an alternative way for improving the conductivity of ionic gels. We incorporating self-adhesiveness to humidity sensors, enable the sensor with more practical uses.